2009
DOI: 10.1177/070674370905400407
|View full text |Cite
|
Sign up to set email alerts
|

Gatekeeper Training as a Preventative Intervention for Suicide: A Systematic Review

Abstract: Suicide prevention remains a challenge across communities in North America and abroad. We examine a suicide prevention effort that is widely used, termed gatekeeper training. There are 2 aims: review the state of the evidence on gatekeeper training for suicide prevention, and propose directions for further research. Method: Studies were identified by searching MEDLINE (PubMed) and PsycINFO from inception to the present for the key words suicide, suicide prevention, and gatekeeper. In addition, a manual scan of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
316
1
19

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(351 citation statements)
references
References 31 publications
15
316
1
19
Order By: Relevance
“…14 In comparisons of the simulated effects of prevention strategies, the largest estimated impacts on declines in suicide were for GP training 17 and coordinated aftercare. 18 Simulated reductions in lethality of method by 20% for selected methods of suicidal behaviour (that is, assuming that interventions were available to reduce lethality of method) also suggested that the largest declines would be achieved with reductions in the lethality of hanging.…”
Section: Summary and Implications Of Findingsmentioning
confidence: 99%
“…14 In comparisons of the simulated effects of prevention strategies, the largest estimated impacts on declines in suicide were for GP training 17 and coordinated aftercare. 18 Simulated reductions in lethality of method by 20% for selected methods of suicidal behaviour (that is, assuming that interventions were available to reduce lethality of method) also suggested that the largest declines would be achieved with reductions in the lethality of hanging.…”
Section: Summary and Implications Of Findingsmentioning
confidence: 99%
“…13 In addition to programs for health professionals, who constitute the primary group of gatekeepers, a substantial number of programs also targeted so-called 'emergent' gatekeepers, that is, community members or staff who have not been formally trained to intervene with someone at risk of suicide but are likely to come into contact with at-risk individuals. 16 These programs were directed to school teachers, professionals such as journalists, family members and other carers, and members of specific regional communities. Gatekeeper education is effective in suicide prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Gatekeeper-programmer implementert i skoler har fokusert på å trene laerere og skolepersonell (Zenere & Lazarus, 1997;Burnette, Ramchand & Ayer, 2015) mens andre programmer har fokusert på å trene jevnaldrende elever til å vaere gatekeepere (Wyman et al, 2010). Unge selvskadere kan ofte kjennetegnes ved sterke følelsesmessige belastninger kombinert med svakere kommunikasjonsferdigheter (Isaac, Katz, Belik, Deane, Enns & Sareen, 2009). Foruten foreldre og foresatte er laerere og skolepersonell de som oftest er i daglig kontakt med barn og unge, og de har dermed mulighet til tidlig å observere endringer hos elever, ta initiativ til samtale og kontakte helsehjelp ved behov.…”
unclassified